Itsbat Nikah in the Legality of Marriage Law in Indonesia: Maslahah Mursalah's Perspective - Abdul Azis; Ali Mutakin (International Journal of Religious and Interdisciplinary Studies, 2024)
Itsbat nikah in Indonesia presents a surprising legal phenomenon because it raises uncertainty about the legality of marriage. The primary purpose of this study is to uncover how itsbat nikah is used as a solution to legally religious marriages that have yet to be officially recorded. The research was carried out with a qualitative approach involving the analysis of literature, legal regulations, and decisions issued by the Religious Court and the Office of Religious Affairs. The study results show that itsbat nikah plays a significant role in legally recognizing marriages that have not been recorded, maintaining legal certainty, and protecting civil rights and inheritance. Implementing itsbat nikah not only meets the legal needs of individuals but also strengthens social order by ensuring that every marriage is legally recognized in society. These findings confirm that itsbat nikah, in the context of maslahah mursalah, supports social justice and legal protection for all Indonesian citizens, emphasizing the importance of this legal mechanism in strengthening the foundation of the family and society.